The Simulation of a Surface Plasmon Resonance Metallic Grating for Maximizing THz Sensitivity in Refractive Index Sensor Application - Asmar Sathukarn; Chia Jia yi; Sakoolkan Boonruang; Mati Horprathum; Khwanchai Tantiwanichapan; Kiattiwut Prasertsuk; Chayut Thanapirom; Woraprach Kusolthossakul; Kittipong Kasamsook (International Journal of Optics)
Nowadays, the simplicity of both designing and fabrication process of a terahertz (THz) resonator-based sensing technique leads to its ongoing development. The consumable THz resonator needs to be easily integrated into an existing terahertz time domain spectroscopy (THz TDS) measurement system. It should also be able to be fabricated in a mass scale with a low production cost. In this work, a metal-coated surface plasmon resonance- (SPR-) based sensor is simulated and designed as a low-cost refractive index sensor utilizing rigorous coupled wave analysis (RCWA). To demonstrate our methodology, we design a gold-coated grating with a polydimethylsiloxane (PDMS) as a substrate, in order to perform quantitative analysis of gasoline-toluene mixture composition, which has a refraction index variation of 0.1 at THz frequency. The grating period is tuned such that its surface plasmon resonance (SPR) frequency matches with the peak frequency of the THz TDS system. Moreover, other grating parameters, i.e., a filling factor and a grating depth, are optimized to increase the sensor sensitivity and sharpen the resonance dip. High sensitivity up to 500 GHz/RIU with a refractive index resolution up to 0.01 is numerically revealed. The H-field of the designed grating is then evaluated to indicate a strong SPR excitation. The well-developed designed grating introduces a promising, low-cost, and easily fabricated THz refractive index sensor.